Ordered Structure Analysis of Prepared Mesoporous Silica Using Small Angle X-Ray Scattering - A.I.W.S. Ramadani; N.S. Pamungkas; N.A. Putrisetya; M.C. Prihatiningsih; M.D. Permatasari; A.A. Nugroho; S. Suyanta; A. Patriati; S. Soontaranon; E.G.R. Putra (Atom Indonesia, 2020)
Ordered pores structureanalysis of mesoporous silica materials using a template of poly(ethylene oxyde)-poly(propylene oxide)-poly(ethylene oxide), PEO-PPO-PEO, triblock copolymer or Pluronics in numerous synthesis conditions has been conducted. Two different length of hydrophilic chain of Pluronics, i.e., P123 (EO20PO70EO20) and F127 (EO106PO70EO106), produced two different fine pore structures, which were basically hexagonal and cubic. A highly ordered pore structure, confirming with many Bragg peaks, was clearly obtained with the lattice parameters in nanometer scale from analyzing the synchrotron small angle X-ray scattering (SAXS) data. Meanwhile, the surface area and pores size of mesoporous silica determined by nitrogen absorption clearly support the analysis of SAXS data, presenting a complete information of pore order characteristics. This paper shows how the synthesis parameters,such as length of hydrophilic chains, silica precursor concentration, Al:Si ratio and synthesis methods, are related to the structure and order of the pores formed. The SAXS patterns show that the pore orderincreases with increasing concentration of sodium silicate and decreases with longer sonication time.